Language of Wider Communication as a Propeller of Early Warning and Early Response in Yobe State - Clifford Irikefe Gbeyonron (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2025)
This work aims to establish the efficacy of language of wider communication (LWC) in coordinating early warning and early response in emergencies in Yobe State, a seemingly fragile state recovering from a fleeting insurgency. To achieve this, a researcher-made questionnaire and a semi-structured interview schedule were respectively administered to 110 and twenty-two 22 respondents who have been participating in Community Peace and Safety Partnership (CPSP) meetings – platforms supported by the British Council and funded by the European Union (EU) in 11 out of the 17 Local Government Areas (LGAs) in the state – to ascertain the use of Hausa language (which is an LWC in the state) in the coordination of the meetings and the implication of that in emergency and conflict management. Similarly, participatory observation was utilized by the researcher to find the language(s) used on the platforms to coordinate the meetings. It was found that the use of the LWC has not only made emergency and conflict management inclusive but also helped in reducing conflicts and risks in the LGAs the platforms are active. This work recommends that for early warning and early response to be effective in a fragile state, the LWC should be prioritized. However, other languages should be developed to enable them to actualize their linguistic rights to participate in public discourse and emergency management.